Emotional Intelligence Versus Willingness to Engage in Unethical Pro-organizational Behavior (UPB). A Brief Research Report - Grabowski, Damian; Kaznocha, Rafał; Stawiarska, Patrycja (Przegląd Psychologiczny, 2024)
Aim: The purpose of this research was to determine the relationship between emotional intelligence (EI) considered as a trait and willingness to engage in unethical pro-organizational behavior (UPB). This research was intended to fill the gap that exists in the field of research on the relationship between emotional intelligence and UPB. Method: The study included 103 people working in companies across Poland. Emotional intelligence (EI) was examined using a questionnaire to diagnose the level of EI constructed by Borkowska and colleagues (2006). Readiness to undertake UPB was measured using the Polish version of the scale of unethical pro-organizational behavior (Grabowski et al., 2019). Results: The study showed that there is a negative relationship between EI and UPB. Mood regulation, emotion perception and empathy, as well as knowledge and emotional insight are negatively related to willingness to undertake UPB. Mood regulation and emotion perception and empathy further appear as downward predictors of readiness to undertake UPB, explaining about 20% of UPB’ variance. Conclusions: The study provided important insights into the relationship between EI and UPB in the group of Polish workers. It can be assumed that emotional intelligence (EI), especially mood regulation, and emotion perception and empathy are factors that reduce readiness to undertake UPB.